History and Current Status of Reclaimed Water Use in Florida - Gurpal S. Toor; Donald P. Rainey (EDIS)
SL308, a 4-page illustrated fact sheet by Gurpal S. Toor and Donald P. Rainey, discusses the history, current status, and importance of reclaimed water use in Florida. Includes references. Published by the UF Department of Soil and Water Sciences, November 2009.